Region- and season-specific exposure to lead in a common North American songbird - M. L. Ohrberg; D. J. Becker; G. M. Filippelli; E. D. Ketterson; S. T. Rader; S. M. Reed; E. J. Williams; A. E. Jahn (Ecotoxicology, 2026)
Although birds have been used globally as bioindicators of heavy metals, the determinants and physiological consequences of their exposure to heavy metals remain poorly understood. The American Robin ( Turdus migratorius ) is a common songbird in a variety of habitats across most of North America that could serve as an ideal sentinel of heavy metal contamination. We evaluated how robin exposure to lead (Pb) varied regionally, seasonally and among demographic groups, and assessed impacts on body condition and reproductive hormone concentrations. We detected higher blood Pb concentrations in robins sampled in a more urban region (Indiana) compared to a more rural region (Alaska). Higher blood Pb concentrations in the more urban region may reflect the robin diet of earthworms, which accumulate lead due to their feeding behavior and could incorporate greater ambient soil lead contamination typical of more urban areas. Blood Pb concentrations were also highest in spring and summer, when robins primarily forage on earthworms. We found no relationship between blood Pb concentrations and body condition, but blood Pb concentrations showed a negative relationship with testosterone in male robins and with estradiol in female robins, suggesting lead may have negative effects on reproductive function. Overall, these results suggest that robins could serve as reliable bioindicators of lead and its impacts on wildlife health across a broad range of ecosystems.